Strategy Analysis for Coworking Space Operator to Sustain in Indonesia Market - Rengganis, Kharisma; Titus, Amol (The Indonesian Journal of Business Administration, 2019)
Abstract - Coworking considered as a disruption in the way people work. People who work in a coworking space have the opportunity to work side by side with people from different companies and profession, thus enabling them to collaborate and learn from like-minded people. The community is what makes a coworking space different from another place to work. Coworking space operator would lease a large size of office space from the building owner and then sublease the space in small sizes to other company. Other than workspace, they also provide all the necessary facilities to support member’s daily activities, such as working chair and desk, photocopy machine and printers, meeting room, and pantry. The main customer of a coworking space which are startups and freelancer, is getting the benefit of a fully equipped low cost office space that can be rented in short period, on monthly basis or daily basis. The coworking space movement was started in 2005 in the US, by a software engineer that wanted to combine the freedom and independence in working as a self-employed worker, along with the good working structure and community of working with others by being an employee. Globally, the number of coworking space is projected to grow from 14,411 in 2017 to just over 30,000 in 2022. In Indonesia, coworking space industry was started in 2010 in Bandung. Today, there are more than 200 coworking space in Indonesia, that spread across major city such as Jakarta, Bali, Surabaya, and Bandung.  Keywords:  business strategy, coworking space in Indonesia, disruption, flexible office space, startup company.